2009
DOI: 10.1590/s0100-69912009000600002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo epidemiológico das fraturas mandibulares em hospital público da cidade de São Paulo

Abstract: OBJETIVO: Analisar a frequência epidemiológica de fraturas mandibulares correlacionando gênero, faixa etária, fatores etiológicos, localização anatômica, e tipos de traços de fratura. MÉTODOS: Estudo retrospectivo nos prontuários de 883 pacientes portadores de fraturas faciais, atendidos no Pronto Socorro do Hospital Geral de Vila Penteado, pelo Serviço de Cirurgia e Traumatologia Buco Maxilo Facial (São Paulo - Brasil), num período de três anos (janeiro de 2004 a dezembro de 2006). RESULTADOS: Dos 883 pacient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
2
0
3
Order By: Relevance
“…Men are significantly more affected than women (Leporace and Paulesini Júnior 2009;Rashid et al 2013;Siwani et al 2014;Flandes et al 2019;Kanala et al 2021), which was confirmed by the present study, but in a lower ratio (3.5:1) than all other regions examined, including Brazil itself. There have been reports that the more severe the facial fracture the more likely it is that a man is involved (Horibe et al 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Men are significantly more affected than women (Leporace and Paulesini Júnior 2009;Rashid et al 2013;Siwani et al 2014;Flandes et al 2019;Kanala et al 2021), which was confirmed by the present study, but in a lower ratio (3.5:1) than all other regions examined, including Brazil itself. There have been reports that the more severe the facial fracture the more likely it is that a man is involved (Horibe et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…There have been reports that the more severe the facial fracture the more likely it is that a man is involved (Horibe et al 2004). In developing countries such as the African and South American continents, the number of men working outside the home is greater than that of womenwho exercise more and are therefore more traumatized (Hassanein 2019;Moshy et al 2020) (Leporace and Paulesini Júnior 2009;Silva et al 2009;Eskitaşcioǧlu et al 2013). An interesting piece of data concerns the correlation between etiology and gender, as men are severely affected by fractures due to road traffic accidents and interpersonal violence and women are affected by physical aggression and falls (Leporace and Paulesini Júnior 2009;Rashid et al 2013;Sand et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed that the epidemiological profile of patients with facial fractures follows that reported by different authors 1,3,[24][25][26] . There was prevalence of men (83%) in both study periods, before and after the law.…”
Section: Idade Idade Idade Idade Idadesupporting
confidence: 88%
“…Dentre os diversos tipos, o trauma de face destaca-se como um dos de maior importância, uma vez que apresenta repercussões emocionais, funcionais e possibilidade de deformidades permanentes. Os principais mecanismos de trauma envolvidos são acidentes automobilísticos, seguidos de agressões, quedas de altura e acidentes esportivos 5 , acidentes de trabalho 3 e traumas por projétil de arma de fogo 6 .…”
Section: Introductionunclassified